2018
DOI: 10.1590/0034-7167-2016-0607
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of intradomiciliary contacts of leprosy cases: perspective of the client in a hyperendemic municipality

Abstract: 164Surveillance of intradomiciliary contacts of leprosy cases: perspective of the client in a hyperendemic municipality Romanholo HSB, et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
16

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
1
14
0
16
Order By: Relevance
“…A special focus should be given to the male population regarding prevention and early detection of the disease [4,6]. We suggest further the integration of specific actions of leprosy health surveillance to the National Policy of Comprehensive Attention to Men’s Health in Brazil, and to the National Policy of Workers’ Health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A special focus should be given to the male population regarding prevention and early detection of the disease [4,6]. We suggest further the integration of specific actions of leprosy health surveillance to the National Policy of Comprehensive Attention to Men’s Health in Brazil, and to the National Policy of Workers’ Health.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, health professionals should be trained systematically to perform diagnosis, treatment and psychosocial rehabilitation of cases. However, several studies revealed operational difficulties of primary health services in the development of leprosy control measures [5,6,32], such as contact tracing [6]. Therefore, municipalities of medium and small size should be prioritized and must receive attention from State and Federal governments in order to strengthen regional support networks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…people, and the physician DISCUSSION https://periodicos.ufpe.br/revistas/revistaenfermagem/index was the health professional who most evaluated these contacts (35%), followed by the nurse (25%) and the physical therapist (10%). Warned, by authors, in another study 23 , that the nurse was the one who most performed the contact examination and that the realization, even by unqualified professionals, according to Ministry of Health regulations, may compromise this control.…”
Section: Introductionmentioning
confidence: 99%